The relationship between Chinese preschool principal leadership styles and teacher leadership: Exploring the mediating effect of psychological capital - Zhang, Limin; Wu, Tingting; Liu, Lijia; Ren, Ping; Lin, Chaopai (Frontiers in Psychology, 2022)
Enhancing teacher leadership is not only one of the approaches to raise teaching and learning, but it is also essential to the success of education reform. Based on the Leader-Member Exchange theory, 294 preschool teachers in China were surveyed and a structural equation model was established to explore the relationship among the participating teachers’ principal leadership style, teacher leadership and psychological capital. The findings revealed a significant positive correlation between transformational and transactional leadership styles and preschool teacher leadership as well as a significant negative correlation between authoritarian leadership style and preschool teacher leadership. Laissez-faire leadership style had no correlation with preschool teacher leadership. Transformational leadership style and transactional leadership style were significantly and positively correlated with psychological capital, while laissez-faire leadership style and authoritarian leadership style were significantly and negatively correlated with psychological capital. Transformational leadership style can positively influence preschool teacher leadership directly and indirectly through psychological capital; transactional leadership style can only positively influence preschool teacher leadership indirectly through the mediating role of psychological capital. Preschool teachers’ leadership can neither be directly influenced by laissez-faire leadership style or authoritarian leadership style, nor be indirectly influenced by them through the mediating role of psychological capital.